2013
DOI: 10.1073/pnas.1301019110
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of human fibroblasts toward a cardiac fate

Abstract: Reprogramming of mouse fibroblasts toward a myocardial cell fate by forced expression of cardiac transcription factors or microRNAs has recently been demonstrated. The potential clinical applicability of these findings is based on the minimal regenerative potential of the adult human heart and the limited availability of human heart tissue. An initial but mandatory step toward clinical application of this approach is to establish conditions for conversion of adult human fibroblasts to a cardiac phenotype. Towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
411
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(439 citation statements)
references
References 37 publications
26
411
0
2
Order By: Relevance
“…Previous studies showed that members of the core cardiogenic gene program Gata4, Mef2c, Tbx5 (and Hand2) (GMT or GMTH) reprogrammed cardiac fibroblasts into spontaneously contracting cardiac-like myocytes in vitro [109] and in vivo [129]. Recapitulation of these studies in human fibroblasts showed that GATA4, TBX5, HAND2 and two MEF2C-regulated miRNAs, miR-133 and miR-1, upregulated the expression of cardiac troponin T and tropomyosin (markers of cardiomyocytes) and created a small subset of spontaneously beating cardiomyocytes [130]. Cumulatively, these studies suggest fibroblasts, or indeed other cells types within and surrounding the infarct, could represent a viable target for cardiomyogenesis.…”
Section: Lessons Learned From Direct Reprogramming Of Fibroblasts Intmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that members of the core cardiogenic gene program Gata4, Mef2c, Tbx5 (and Hand2) (GMT or GMTH) reprogrammed cardiac fibroblasts into spontaneously contracting cardiac-like myocytes in vitro [109] and in vivo [129]. Recapitulation of these studies in human fibroblasts showed that GATA4, TBX5, HAND2 and two MEF2C-regulated miRNAs, miR-133 and miR-1, upregulated the expression of cardiac troponin T and tropomyosin (markers of cardiomyocytes) and created a small subset of spontaneously beating cardiomyocytes [130]. Cumulatively, these studies suggest fibroblasts, or indeed other cells types within and surrounding the infarct, could represent a viable target for cardiomyogenesis.…”
Section: Lessons Learned From Direct Reprogramming Of Fibroblasts Intmentioning
confidence: 99%
“…Cumulatively, these studies suggest fibroblasts, or indeed other cells types within and surrounding the infarct, could represent a viable target for cardiomyogenesis. However, reprogramming of cell identity, in both pluripotency and direct reprogramming approaches, is an inefficient process and current strategies result in off-target effects in other cell types within and outside the heart [109,124,[130][131][132]. Few studies have interrogated epigenomic profiles after fibroblast direct reprogramming to cardiomyocytes but epigenomic reconfiguration of histone marks (H3K4me3 and H3K27me3) and DNA methylation patterns at sarcomeric gene loci has been validated in mouse [109,133,134] and human induced cardiomyocytes [109,[133][134][135].…”
Section: Lessons Learned From Direct Reprogramming Of Fibroblasts Intmentioning
confidence: 99%
“…Nam et al reported that a combination of Gata4, Hand2, Tbx5, Myocd, miR-1, and miR-133 induced 13 % of adult HCFs to express cardiac troponin T protein and that a small subset of the iCMs exhibited spontaneous contractility after 11 weeks in culture [ 15 ]. Islas et al reported that transient overexpression of Ets2 and Mesp1 could reprogram human dermal fi broblasts into cardiac progenitor-like cells [ 16 ].…”
Section: Gata4/mef2c/tbx5/myocd/mesp1 Reprogram Human Fibroblasts Intmentioning
confidence: 99%
“…Delivery of cardio-specific transcription factors and/or or microRNAs to infarcted mouse hearts had also been shown to result in direct transdifferentiation of fibroblasts into cardiomyocyte-like cells in vivo and improvement of the functioning of the damaged myocardium [82,84,85]. Human fibroblasts have also been induced to transdifferentiate into cardiomyocyte-like cells in vitro using basically the same cardio-specific transcription factors (GATA4, HAND2, TBX5 and MEF2C) [82] or transcription factors (GATA4, HAND2, TBX5, and myocardin) plus microRNAs (miR-1 and miR-133) [86].…”
Section: Cardiomyocytes Derived By Reprogramming Of Somatic Cellsmentioning
confidence: 99%